The Role of Facilities in Shaping Service Quality, Comfort, and Passenger Satisfaction: Evidence from the Banyuwangi Airport Waiting Room - Agusinta, Lira (Universitas Djuanda, 2025)
This study investigates the impact of airport facilities on visitor satisfaction at Banyuwangi International Airport, with service quality and comfort as mediating variables. Using the Expectation-Confirmation Theory (ECT) as the theoretical framework, the research explores how passenger experiences in the airport waiting room shape overall satisfaction. A quantitative approach was applied. This research was conducted at Banyuwangi International Airport involving 80 respondents, with the determination of the sample size based on Roscoe's guidelines (multiplying the number of variables by 20), sampling was carried out accidentally to select respondents based on accessibility and availability. Data was analyzed using path analysis via SmartPLS. The results show that facilities significantly influence service quality and comfort and directly affect visitor satisfaction. Furthermore, service quality substantially mediates the relationship between facilities and satisfaction, reinforcing its critical role in shaping positive passenger perceptions. However, comfort was found to have no significant direct or mediating effect on satisfaction. These findings suggest that service quality plays a more substantial role in determining satisfaction than physical comfort in the context of regional airports. The study highlights the importance of integrating the provision of high-quality services with infrastructure development to enhance the passenger experience with improvements in physical infrastructure (environmental conditions, layout and functionality of spaces, signs, symbols, and artifacts), operational efficiency, and warm service from service officers are highly recommended to provide a more positive and memorable travel experience.